RI 2374 Summary Of Investigations Of Dust And Ventilation In Metal Mines - With A Bibliography - D. Hurrington (The National Institute for Occupational Safety and Health (NIOSH), 1922)
For severlrl 1e1.rs the Bureau of Mines has studied dust and ventili in metal mines a.s a.tfeoting the hea.l th, safety, and efficiency of underground workers. From its beginning this work haa been directed by G, s. Rice, chief mining engineer, A. cooperative agreement was ma.de in 1915 with the u. s. Publi􀀿 Health Service; since that time tield obmervations 1n metal mines in Arizona, California, Idaho, Montana, Michigan and Nevada, and less extensive observation, in several other States have been made by mining engineers of the U, s. Bureau of Mines, and doctors of the u. s. Pu.blic Heal.th Service. Most of the analyt:J:eal work has been done by chemists, petrographers, and other specialists in the Pittsburgb station ot the Bureau of Mines, Numerous articles have been printed by the otticial and the technical press on this important in•estigation; 1n response to the need for a btiet bibliography of this literature. it has been compiled to facilitate accp1,intance with published data ot1. the subject,